COMPETITIVENESS AND INDUSTRIAL NATIONAL PLAN - Flores Konja, Adrián Alejandro (2010)
This article, which discusses an exploratory investigation analyses the concepts of the National Competitiveness Plan, proposed by the National Competitiveness Council, determining that there is in it an explicit Industrial Plan, which defines the location of Peru in the international division of work different than the “Plan” de facto subjecting Peru to the production of minerals and agricultural products, or tourism, without getting into the industry. Analyse Peru´s specialization in raw minerals and other primary extractive products, and their consequences. The article analizes how was formulated the National Projects in the republican history too in relation to the industrial plan and gives an assessment of why theses effort failed. It also notices the requirements in infrastructure, education and science funding needed to implement a real industrial plan. Finally. it proposes some elements that can be included in the Industrial Plan, according to the country’s natural vocation and the demands of scientific and technological development of mankind.